SINTASAN DAN PERTUMBUHAN IKAN PATIN SIAM (Pangasianodon hypopthalmus) AKIBAT RESPON FISIOLOGIS YANG BERBEDA PADA BERBAGAI TINGKAT KALSIUM MEDIA - Muliani .; Djokosetiyanto .; Tatag Budiarti (Universitas Sriwijaya, 2013)
ABSTRACT Calcium is one of macromineral that needed by fish for physiological processes such as osmoregulation, enzyme regulation, ossification and cell permeability. This study aimed to determine the optimum concentration of calcium carbonate (CaCO3) at 3 ppt salinity of media and evaluated the effects of adding calcium to physiological conditions and the affect to the survival rate and growth of catfish. The study was conducted in two stages; the first stage was determined the optimum concentration of calcium, the second stage was evaluated the effect of calcium on the physiological condition of fish. Randomized completely design with 4 treatments and 3 repitations (A. 3 ppt + 0 mg/L CaCO3, B. 3 ppt + 50 mg/L CaCO3, C. 3 ppt + 100 mg/ L CaCO3, D. 3 ppt + 150 mg/L CaCO3) were used in this study. The results showed that the salinity of media with the addition of calcium can reduce levels of osmotic performance, oxygen consumption, and blood glucose levels, and it can increase the feed efficiency and daily growth rate. Treatment C (3 ppt + 100 mg/L) showed the best physiological condition among other treatments. Keywords : Calcium; Salinity; Catfish; Pangasianodon hypopthalmus